Lingua, memoria e identità nei racconti dei migranti ispanoamericani (Altre Modernità, 2014)
In a wide-ranging theoretical framework, principally based upon discourse analysis and the studies on language and identity, this article explores the construction of identity in a corpus of oral narratives collected among the Spanish speaking communities in Milan, by means of sociolinguistic and biographic interviews, seen as a complex event in which both parties act as active participant-observers. The study focuses on the features of these life stories, taking into account the ways in which the immigrants compare the two worlds an collocates themselves between the two cultures, the function of code-switching, the linguistic expression of ‘agency’ (Giddens 1979) and the use of deictics.